(untitled) (International Journal of Academic Research in Progressive Education and Development, 2023)
The quality of the environment is thought to have deteriorated at an alarming rate. Hence environmental education and awareness become critical steps to mitigate the issue. The current paper attempts to undertake a Systematic Literature Review (SLR) that focuses on the student’s knowledge, attitude, awareness, and behavior toward the environment to identify the relationship among these variables as well as the methods for improving the environment. The PRISMA Statement (Preferred Reporting Items for Systematic reviews and Meta-Analyses) is used in the review process. A total of eleven articles that meet the inclusion and exclusion criteria were collected from three databases: Scopus, Web of Science, and ProQuest. Seven studies examined the relationship among four domains (environmental knowledge, attitude, awareness, and behavior). Two studies found discussed the relationship between environmental knowledge and environmental attitude. While one study only focused on environmental knowledge. Only two publications uncover how important it is to include environmental education in the learning process if we want to make a society that is aware of and cares about the environment. Also, several alternatives could be used to help students learn about the environment, such as outdoor environmental education and teaching materials based on local wisdom.